PD-1 inhibitor versus bevacizumab in combination with platinum-based chemotherapy for first-line treatment of advanced lung adenocarcinoma: A retrospective-real world study - Huang, Zhe; Zhou, Chunhua; Xiong, Yi; Yang, Feng; Zeng, Fanxu; Jiang, Wenjuan; Zhang, Yongchang; Yang, Haiyan; Liu, Li; Zeng, Liang; Yang, Nong; Wang, Zhan (Frontiers in Oncology, 2022)
Background Chemotherapy combined with immunotherapy or anti-vascular therapy is both recommended by guidelines for first-line treatment of lung adenocarcinoma. However, no head-to-head clinical trial has ever compared which strategy is the optimal choice. This real-world retrospective study was done to compare the efficacy and treatment-related adverse events of immunotherapy and bevacizumab in combination with chemotherapy. Patients and methods From January 2018 to March 2021, we retrospectively collected 276 patients with advanced lung adenocarcinoma managed with chemotherapy combined with bevacizumab or PD-1 inhibitors at our center. Among them, 139 patients were treated with chemotherapy combined with bevacizumab, while 137 patients were treated with chemotherapy combined with PD-1 inhibitors. After receiving four cycles of combination therapy, all patients received maintenance therapy until disease progression. Progression‐free survival (PFS), overall response rate (ORR), overall survival (OS), disease control rate (DCR), and adverse events (AE) were analyzed between the two groups. Results Compared to patients who received anti-vascular therapy, patients who underwent immunotherapy achieved better PFS (7.3 months vs. 10 months, p = 0.002) while ORR (40.9% vs. 51.1%, p = 0.093), as well as OS (18 months vs. 24 months, p = 0.060), had no statistical difference between the two groups. In the PD-L1-negative population, there was no statistical difference in PFS and OS between the two groups. (8.0 months VS. 6.0 months, p = 0.738; and 19 months vs. 13 months, p = 0.274). In the PD-L1-positive population, there was a significant benefit in PFS in the population receiving immunotherapy (7.0 months vs. 10.0 months, p = 0.009). Proteinuria and hypertension occurred more frequently in the bevacizumab-treated group (p = 0.001 and p = 0.002), whereas immune-related pneumonia and hypothyroidism occurred more frequently in the immunotherapy-treated group (p = 0.007 and p = 0.030). Conclusions The addition of a PD-1 inhibitor was superior to bevacizumab in terms of PFS among patients with advanced lung adenocarcinoma. PD-L1-positive patients appeared to exhibit better PFS, OS, and ORR. Toxic reactions were manageable in both groups.